Reduction of COD and pH of Textile Industrial Effluents by Aquatic Macrophytes and Algae (Journal of Bangladesh Academy of Sciences, 2010)
Effluents samples collected from post discharge of equalization tanks of local compositetextile mills of Saver were treated with aquatic macrophytes, algae and their combination. Theywere found to be effective for the reduction of chemical oxygen demand (COD) and pH. Sixty nineper cent of COD was reduced with the combination treatment of Nostoc, Eichhornia crassipes andPistia stratiotes. With the combination treatment of Nostoc and E. crassipes reduced 65 per centCOD in glass containers. pH was reduced from 11.2 to 8.6. Between earthen and glass containers,glass container was found to be more effective.Key words: Industrial effluents; COD; pH; Aquatic macrophytes; AlgaeDOI: 10.3329/jbas.v34i1.5487Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 9-14, 2010